Antimicrobial Resistance in African Great Apes - Coch Tanguy Floyde Tanga; Patrice Makouloutou-Nzassi; Pierre Philippe Mbehang Nguema; Ariane Düx; Silas Lendzele Sevidzem; Jacques François Mavoungou; Fabian H. Leendertz; Rodrigue Mintsa-Nguema (Antibiotics, 2024)
Background/Objectives: Antibiotic-resistant bacteria pose a significant global public health threat that demands serious attention. The proliferation of antimicrobial resistance (AMR) is primarily attributed to the overuse of antibiotics in humans, livestock, and the agro-industry. However, it is worth noting that antibiotic-resistant genes (ARGs) can be found in all ecosystems, even in environments where antibiotics have never been utilized. African great apes (AGAs) are our closest living relatives and are known to be susceptible to many of the same pathogens (and other microorganisms) as humans. AGAs could therefore serve as sentinels for human-induced AMR spread into the environment. They can potentially also serve as reservoirs for AMR. AGAs inhabit a range of environments from remote areas with little anthropogenic impact, over habitats that are co-used by AGAs and humans, to captive settings with close human–animal contacts like zoos and sanctuaries. This provides opportunities to study AMR in relation to human interaction. This review examines the literature on AMR in AGAs, identifying knowledge gaps. Results: Of the 16 articles reviewed, 13 focused on wild AGAs in habitats with different degrees of human presence, 2 compared wild and captive apes, and 1 study tested captive apes alone. Ten studies included humans working with or living close to AGA habitats. Despite different methodologies, all studies detected AMR in AGAs. Resistance to beta-lactams was the most common (36%), followed by resistance to aminoglycosides (22%), tetracyclines (15%), fluoroquinolones (10%), sulphonamides (5%), trimethoprim (5%), macrolide (3%), phenicoles (2%) and fosfomycin (1%). Conclusions: While several studies suggest a correlation between increased human contact and higher AMR in AGAs, resistance was also found in relatively pristine habitats. While AGAs clearly encounter bacteria resistant to diverse antibiotics, significant gaps remain in understanding the underlying processes. Comparative studies using standardized methods across different sites would enhance our understanding of the origin and distribution of AMR in AGAs.